2008
DOI: 10.1038/hdy.2008.43
|View full text |Cite
|
Sign up to set email alerts
|

The MHC and non-random mating in a captive population of Chinook salmon

Abstract: Detailed analysis of variation in reproductive success can provide an understanding of the selective pressures that drive the evolution of adaptations. Here, we use experimental spawning channels to assess phenotypic and genotypic correlates of reproductive success in Chinook salmon (Oncorhynchus tshawytscha). Groups of 36 fish in three different sex ratios (1:2, 1:1 and 2:1) were allowed to spawn and the offspring were collected after emergence from the gravel. Microsatellite genetic markers were used to assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
4
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(122 citation statements)
references
References 81 publications
7
109
4
1
Order By: Relevance
“…Studies in Atlantic salmon (Landry et al, 2001;Consuegra and de Leaniz, 2008) and Chinook salmon (Neff et al, 2008) revealed that reproductive success was positively correlated with MHC class II allelic distance of mates (disassortative). In these studies, females and males were allowed to spawn freely without interference and it is not possible to differentiate between the impact of female choice and male competitiveness pre-and post-spawning on the reproductive success.…”
Section: The Mhc and Fertilization Successmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in Atlantic salmon (Landry et al, 2001;Consuegra and de Leaniz, 2008) and Chinook salmon (Neff et al, 2008) revealed that reproductive success was positively correlated with MHC class II allelic distance of mates (disassortative). In these studies, females and males were allowed to spawn freely without interference and it is not possible to differentiate between the impact of female choice and male competitiveness pre-and post-spawning on the reproductive success.…”
Section: The Mhc and Fertilization Successmentioning
confidence: 99%
“…Neff et al (2008) detected that females produced more offspring with MHC class II dissimilar males in Chinook salmon but since individuals were allowed to spawn without interference, it was impossible to disentangle female choice prior to and post mating. However, it allows to hypothesize that CFC might be biased towards MHC class II dissimilar males…”
Section: Introductionmentioning
confidence: 99%
“…Among species with conventional sex roles, captive male chinook salmon (Oncorhynchus tshawytscha) also mated randomly with respect to female MHC genotype (Neff et al 2008). …”
mentioning
confidence: 99%
“…DNA was extracted from parents and offspring, and genetic variation was then evaluated using seven microsatellite loci (for details see Neff et al 2008). Parental allocation was based on maximum likelihood procedures implemented in the program Cervus (v. 3.0, Marshall et al 1998;Kalinowski et al 2007).…”
Section: Methodsmentioning
confidence: 99%
“…We predicted that intrasexual aggression would correlate with reproductive success, as dominant females may obtain preferred nest sites, and dominant males may monopolize access to spawning females. We also examined how intersexual aggression related to MHC genotypes, as we predicted that female aggression towards MHC similar males may be the mechanism that leads to the higher observed MHC amino acid divergence in a female's offspring than expected by chance (Neff et al 2008). We likewise examined the role of MHC genotype in male aggression towards females.…”
Section: Introductionmentioning
confidence: 99%